ANALISIS PENDAPATAN PENJUALAN KONTER QIANA CELL PADA MASA PANDEMI COVID-19 : ANALISIS PENDAPATAN PENJUALAN KONTER QIANA CELL PADA MASA PANDEMI COVID-19 - Muta Ali, Abdul; Hayatie, Marliza Noor; Nurani, Muhammad Fahmi; Annisa, Rahma (P3M Politeknik Negeri Tanah Laut, 2021)
This research aims to find out the sales of Qiana Cell Counter in 2020 from January to December. Qualitative and quantitative research methods by attaching sales data based on profit and deepening with interviews. The results of the study provide data that sales at the Qiana Cell counter increased and increased from January to December 2020 from Counters to 4 Counters. This increase is also influenced by HR and strategic location and also the sales strategy carried out by Qiana Cell.